1987
DOI: 10.1080/07391102.1987.10506395
|View full text |Cite
|
Sign up to set email alerts
|

B-Z Junctions in Supercoiled pRW751 DNA Contain Unpaired Bases or Non-Watson-Crick Base Pairs

Abstract: Structural distortions on the boundary between right-handed and left-handed DNA segments in negatively supercoiled plasmid pRW751 (a derivative of pBR322 containing (dC-dG)13 and (dC-dG)16 segments) were studied by means of osmium tetroxide, pyridine and glyoxal. These two probes react preferentially with single-stranded DNA, but only the latter requires non-paired bases for the reaction. Nuclease S1 and testing of the inhibition of BamHI cleavage (whose recognition sequences GGATCC lie on the "outer" boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1988
1988
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…We used nuclease Sl to recognize and cleave regions made permanently single-stranded due to the chemical modification, i.e. the technique which was successfully applied in the osmium tetroxide probing of cruciform structures [16,17], B-Z junctions [18,19] and other unusual local DNA structures [20,21]. The mechanism of action of nuclease Sl is, however, not known in detail, and it has been shown [19,23] that this enzyme does not always recognize one or a few chemically modified nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…We used nuclease Sl to recognize and cleave regions made permanently single-stranded due to the chemical modification, i.e. the technique which was successfully applied in the osmium tetroxide probing of cruciform structures [16,17], B-Z junctions [18,19] and other unusual local DNA structures [20,21]. The mechanism of action of nuclease Sl is, however, not known in detail, and it has been shown [19,23] that this enzyme does not always recognize one or a few chemically modified nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol used in this study was similar to the published one (21 ): chemically modified supercoiled DNA was cleaved with BgU and subsequently digested by the respective poly linker restrictases. Modification of pPK2 DNA was carried out in 0.2 M NaCl with TE buffer (pH 7.8) i.e., at ionic strength used in our previous experiments (17,18,21,22). No inhibition of the above restrictases was observed either with Os0 4 modified pUC18 (not shown) or with unmodified pPK2 (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical probes (15)(16)(17)(18)(19)(20) and especially osmium tetroxide complexes (2,3,15,17,18,(21)(22)(23) have proved to be one of the most powerful techniques in their research. It has been shown that osmium binding sites in DNA strands can be detected by means of nuclease Sl (18,(21)(22)(23), inhibition of Bam HI cleavage at the B-Z junction (2,17,18,21 ), and at single-nucleotide resolution by piperidine cleavage and electrophoresis in sequencing gel (15,22,23). In this paper an attempt has been made for the first time to apply all these three techniques simultaneously at one plasmid to compare the sensitivity and resolving power of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…KMnO4 oxidizes DNA bases reacting mainly with thymine and to a much lesser extent with cytosine and guanine, i.e., its reactivity towards bases is similar to that of osmium tetroxide itself [18] and to some extent also to that of Os,bipy [5,26]. A combination of chemical probes in the studies of the DNA structure in vitro has been very useful [17,19,22,27] and one can expect that it will be even more important in the studies of the DNA structure in the cell mainly due to the complexity of the environment inside the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Site-specific modification of B-Z junctions can be detected on the basis of inhibition of BamHI cleavage [6][7][8]10,11,16,17]. This method is very simple and sensitive [16].…”
Section: Site-specific Modification Of the B-z Junctionmentioning
confidence: 99%